2011
DOI: 10.1371/journal.pone.0021996
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Hydroxynitrile Lyase in Cassava Roots Elevates Protein and Free Amino Acids while Reducing Residual Cyanogen Levels

Abstract: Cassava is the major source of calories for more than 250 million Sub-Saharan Africans, however, it has the lowest protein-to-energy ratio of any major staple food crop in the world. A cassava-based diet provides less than 30% of the minimum daily requirement for protein. Moreover, both leaves and roots contain potentially toxic levels of cyanogenic glucosides. The major cyanogen in cassava is linamarin which is stored in the vacuole. Upon tissue disruption linamarin is deglycosylated by the apolplastic enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…The cassava tuber root is rich in starch (30% starch/g fresh weight) [26]. HXKs play a key role in cassava starch synthesis [19].…”
Section: Introductionmentioning
confidence: 99%
“…The cassava tuber root is rich in starch (30% starch/g fresh weight) [26]. HXKs play a key role in cassava starch synthesis [19].…”
Section: Introductionmentioning
confidence: 99%
“…Consumption of residual cyanogens (linamarin and lotaustralin) in incompletely processed cassava roots can cause various health disorders that render a person unsteady and uncoordinated [12]. Hydroxynitrile lyase (HNL) catalyzes the conversion of acetone cyanohydrin to cyanide and is expressed predominantly in the cell walls and laticifers of leaves, compared with tuberous roots, which exhibit very low [10].…”
Section: Hydrogen Cyanide Contentmentioning
confidence: 99%
“…Hydroxynitrile lyase (HNL) catalyzes the conversion of acetone cyanohydrin to cyanide and is expressed predominantly in the cell walls and laticifers of leaves, compared with tuberous roots, which exhibit very low [10]. Transgenic cassava over-expressing HNL was shown to display significantly reduced acetone cyanohydrin levels and exhibited increased cyanide volatilization in processed or homogenized roots [12]. It has been shown that the genomic region surrounding the cytochrome P450, CYP79D3, contains all genes required for cyanogenic glucoside biosynthesis in cassava [13].…”
Section: Hydrogen Cyanide Contentmentioning
confidence: 99%
“…It has been demonstrated that cyanogens provide reduced nitrogen substrates for amino acid synthesis in cassava roots and, therefore, manipulation of linamarin metabolism in cassava might elevate root amino acid pools and promote total protein biosynthesis [6] . Overexpression of hydroxynitrile lyase, the enzyme that catalyzes the conversion of acetone cyanohydrin to cyanide, in cassava roots was reported to increase overall protein content [18] . In fact, efforts to develop high protein cassava by conventional breeding have also been made by the investigation of crude protein content in cassava roots Fig.…”
Section: Amino Acid Profile and Identification Of Cassava Proteinsmentioning
confidence: 99%